Diversity of sex chromosomes in Sulawesian medaka fishes. (21st August 2022) - Ansai, Satoshi; Montenegro, Javier; Masengi, Kawilarang W. A.; Nagano, Atsushi J.; Yamahira, Kazunori; Kitano, Jun
Abstract: Recent genetic and genomic studies have revealed tremendous diversity in sex chromosomes across diverse taxa. Closely related species with different sex chromosomes provide us excellent opportunities to investigate the driving forces and the consequences of sex chromosome turnover. In the present study, we investigated the diversity of sex chromosomes of 13 Oryzias species from Sulawesi, Indonesia, which diversified during the last 4.86 million years. Using pooled sequencing, we found sex chromosomes in nine species that all had XY systems, with a species being possibly modified by multiple loci. Seven species ( O. woworae, O. asinua, O. wolasi, O. matanensis, O. celebensis, O. hadiatyae, and O. dopingdopingensis ) share linkage group (LG) 24 as sex chromosomes; however, they differed in the length and magnitude of sequence divergence between the X and Y chromosomes. The sex chromosome of O. eversi was LG4, which has not been reported as a sex chromosome in any other medaka species. In O. sarasinorum, LG16 and LG22 are associated with sex. Although LG16 was found to be sex‐linked in another medaka species previously examined, the sex‐determining regions did not overlap. No significant signatures for sex chromosomes were identified in the other four species ( O. marmoratus, O. nigrimas, O. nebulosus, and O. orthognathus ). Frequent turnovers and the great diversity of the sex chromosomes will make Sulawesian medaka species a model system for investigating the driving forces and consequences of sex chromosome turnover. Abstract : In this study, we investigated the diversity of sex chromosomes of 13 medaka fishes (genus Oryzias ) from Sulawesi, Indonesia using pooled sequencing. Sex chromosomes were identified in 9 species that all had XY systems with a species being possibly modified by multiple loci, whose positions are indicated as linkage groups (LG) according to numbering the chromosomes in Japanese medaka.